Configuring Supply Chain as a Strategy of Enhancing Firm Performance: A study on Manufacturing Sector in Kenya - Benedict Mutinda Kimwaki (Rowter Journal, 2023)
This paper explored the role played by supply chain configuration on the performance of manufacturing sector in Kenya. Kenya’s manufacturing sector has come a long way in contributing to the country’s economic growth and development. However, the past decade has not been favourable for the sector, as it has recorded a significant decline in performance and growth characterized by loss-making, and declining production. With supply chain taking a huge portion of the industry’s operations, it raises the question on the extent to which supply chain of the manufacturing firms in Kenya has been aligned to suite the interests of suppliers, service providers, and customers as the key stakeholders in the supply chain process. The paper was anchored on the Supply Chain Operations Reference (SCOR) model which describes the essence of organizations to map, measure, and optimize their supply chain processes. Informed by a descriptive research design, primary data was collected from 160 manufacturing firms in Kenya using a questionnaire. Descriptive and inferential statistics were used to analyse the data. The findings revealed that supply chain configuration was significant in determining the performance of the manufacturing industry in Kenya. The findings revealed that configuring supply chain through promoting relationship with customers and suppliers played a significant role in reducing the costs of operations, enhancing quality and productivity thus enhancing profitability of manufacturing firms. A recommendation is therefore drawn that for the Kenya’s manufacturing sector to regain its strength and performance, there is need for the management to put more emphasis on supply chain processes by instigating strategies that enhance configuration of the supply chain network.